Dyslipidemia and mean lipid profile in patients with liver cirrhosis - Sohail, Sajjad; Mustafa, Muhammad Imran; Shaheen, Mohammad Arif; Ali, Qazi Masroor; Tariq, Mohammad Sohail (International Journal of Research in Medical Sciences, 2020)
Background: Patients with liver disorders are often found to have deranged lipid profile. Clear decline is observed in the levels of cholesterol as well as TG among individuals having severe hepatitis and liver failure as synthesis of lipoprotein is reduced. This study was done to determine the frequency of dyslipidemia and the mean lipid profile values in patients of liver cirrhosis. Methods: A cross sectional, descriptive study, done at the Department of Medicine, Medical Unit-1, Bahawal Victoria Hospital, Bahawalpur, from July to December 2019. A total of 246 patients presented with cirrhosis of liver of age 20-60 years and both genders were included. Analysis for serum total cholesterol (TC) level, serum triglycerides level, low density lipoprotein (LDL) and high density lipoprotein (HDL) were done and findings were noted. Results: Mean age was 51.67±6.21 years. Out of the 246 patients, 153 (62.20%) were male and 93 (37.80%) were females with male to female ratio of 1.6:1. Mean values of lipid were, LDL cholesterol 95.76±29.65 mg/dl, HDL 43.37±11.46 mg/dl, TC 147.51±42.69 mg/dl and TG 101.29±21.59 mg/dl. Dyslipidemia was found in 59 (23.98%) patients, whereas there was no dyslipidemia in 187 (76.02%) patients. Conclusions: Frequency of dyslipidemia in cirrhotic patients is high. Evaluating patients of liver cirrhosis, dyslipidemia need to be considered for early recognition and analysis.